2006
DOI: 10.1007/s10549-006-9296-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuronal protein synuclein gamma gene as a novel marker for breast cancer prognosis

Abstract: Synucleins are emerging as central players in the fundamental neural processes and in the formation of pathologically insoluble deposits characteristic of neurodegenerative diseases. However, synuclein gamma (SNCG), previously identified as a breast cancer specific gene (BCSG1), is also highly expressed in breast carcinomas, but not expressed in normal or benign breast tissues. We analyzed SNCG gene expression in 93 clinical breast specimens and associated it with clinical outcome. Overall SNCG mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 23 publications
5
47
2
Order By: Relevance
“…Expression of SNCG in breast cancer cells leads to a significant increase in motility and invasiveness in vitro and a profound augmentation of metastasis in nude mice (Jia et al, 1999). Consistent with the ability to confer metastatic potential to breast cancer cells, we recently demonstrated that patients with SNCG-positive breast cancer have statistically higher incidence for metastasis compared with patients with SNCG-negative cancer (Wu et al, 2006). In addition, a recent study also indicates a strong association between SNCG protein expression in primary tumors and distant metastasis in diversified cancer types, including liver, esophagus, colon, gastric, lung, prostate, cervical and breast cancer .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Expression of SNCG in breast cancer cells leads to a significant increase in motility and invasiveness in vitro and a profound augmentation of metastasis in nude mice (Jia et al, 1999). Consistent with the ability to confer metastatic potential to breast cancer cells, we recently demonstrated that patients with SNCG-positive breast cancer have statistically higher incidence for metastasis compared with patients with SNCG-negative cancer (Wu et al, 2006). In addition, a recent study also indicates a strong association between SNCG protein expression in primary tumors and distant metastasis in diversified cancer types, including liver, esophagus, colon, gastric, lung, prostate, cervical and breast cancer .…”
Section: Discussionsupporting
confidence: 64%
“…SNCB and SNCG have also been recognized to play a role in the pathogenesis of PD and Lewy bodies cases (Galvin et al, 1999;Duda et al, 2000). Although synucleins are highly expressed in neuronal cells and are abundant in presynaptic terminals, they have also been implicated in non-neural diseases, particularly in the hormone responsive cancers of breast (Ji et al, 1997(Ji et al, , 1999Jiang et al, 2003Jiang et al, , 2004Inaba et al, 2005;Wu et al, 2003Wu et al, , 2006Gupta et al, 2003a, b) and ovary (Lavedan et al, 1998;Bruening et al, 2000;Liu et al, 2000;Lu et al, 2000;Pan et al, 2002;Gupta et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…SNCG predicts poor clinical outcome in BC (Guo et al, 2007;Wu et al, 2007). When overexpressed, SNCG stimulates growth of hormone-dependent BC cells both in vitro and in nude mice (Jiang et al, 2003;Jiang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…have indicated that overexpression of Á-synuclein led to a significant increase in motility and invasiveness in cell culture and to a profound augmentation of metastasis in nude mice (10)(11)(12)(13)24,25). ·-, ß-synuclein were also expressed in some nervous system cancers, and breast and ovarian cancer (17,18).…”
Section: -------------------------------------------------mentioning
confidence: 99%
“…The following studies showed that Á-synuclein was aberrantly expressed in various types of cancer, especially in advanced stages of the diseases, but rarely expressed in tumor-matched non-neoplastic adjacent tissues (NNAT) (10). Patients with Á-synuclein protein-positive breast cancer have a significantly shorter disease-free survival and overall survival period compared to patients with no Á-synuclein expression (11,12). Furthermore, studies to date indicate that overexpression of Á-synuclein can stimulate proliferation, and induce invasion and metastasis of breast cancer cells in vitro assays as well as in animal models (13).…”
Section: Introductionmentioning
confidence: 99%